2022
DOI: 10.1002/cjoc.202200034
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Bohemamines and Synthesis of Methylene‐Bridged Chimeric Derivatives through Natural Product Chimera Strategy

Abstract: Five new pyrrolizidine alkaloids, bohemamines J-N (1-5), were isolated from Streptomyces sp. CPCC 200497. Their structures were assigned based on detailed spectroscopic analysis and semisynthesis. Bohemamine J (1) possesses a new chimeric skeleton derived from bohemamine A (6) and phenylacetaldehyde. Inspired by the nonenzymatic formation mechanism of the methylene-bridged dimers isolated from this strain, we synthesized a series of chimeric derivatives (8, 9, and 12-23) through natural product chimera strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Further studies of the Streptomyces sp. CPCC 200497 strain led to the discovery of five new bohemamines J-N [63].…”
Section: Functions Of Microbial Pas In the Environment And Their Sign...mentioning
confidence: 99%
“…Further studies of the Streptomyces sp. CPCC 200497 strain led to the discovery of five new bohemamines J-N [63].…”
Section: Functions Of Microbial Pas In the Environment And Their Sign...mentioning
confidence: 99%
“…The planar structures of 1 and 2 were established based on 2D NMR spectra, and their absolute configurations were clarified by a combination of computational chemistry and synthetic chemistry. The results clarified that hennaminal ( 1 ) possesses a very rare functional group, β,β-diamino unsaturated ketone, and hennamide ( 2 ) contains a reactive N -acyl pyrrolinone moiety, which spontaneously induces self-dimerization. An evaluation of biological activities using natural 1 and synthetic 2 revealed that hennaminal ( 1 ) and hennamide ( 2 ) had weak selective antitrypanosomal activity.…”
mentioning
confidence: 92%
“…We recently discovered two new cyanobacterial metabolites, hennaminal ( 1 ) and hennamide ( 2 ). Hennaminal ( 1 ) possesses a very rare functional group, β,β-diamino unsaturated ketone, which has only been found in bohemamine-type natural products so far . Hennamide ( 2 ) possesses a reactive N -acyl pyrrolinone moiety, which provides both nucleophilicity and electrophilicity.…”
mentioning
confidence: 99%
“…Some polycyclic derivatives of polyenic macrolactams are proposed to be produced through nonenzymatic intramolecular cycloadditions and oxidative cyclizations, such as is the case with heronamides, verticilactam, and macrotermycins . Nonenzymatic reactions have been found to be involved in the formation of many complex natural products, including, for example, chimedermycins, pyonitrins, dibohemamines, and discoipyrroles . Thus, as with enzymatic processes, nonenzymatic reactions also play an important role in the formation of natural products.…”
mentioning
confidence: 99%